Metabolomics of ginger based on ultra-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry technology. (23rd April 2021) - Yan, Hui; Zou, Dongqian; Zhou, Guisheng; Yu, Hanwen; Li, Penghui; Wang, Tianshu; Bao, Beihua; Guo, Sheng; Duan, Jinao
Abstract: Objectives: Dried ginger and ginger are the same type of medicine and food. The differential components of ginger and dried ginger, dried ginger and ginger charcoal were investigated. Materials and Methods: The experimental materials were divided into three sample groups: the ginger group, dried ginger group, and ginger charcoal group. The ginger group, dried ginger group, and ginger charcoal group were qualitatively analyzed by ultra-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry. The data were processed by Marker View Software. Principal component analysis and orthogonal partial least-square discriminant analysis were performed with SIMCA 13.0 Software. The differential components of the ginger and dried ginger groups as well as the dried ginger and ginger charcoal groups with a variable importance in the projection > 2 ( P < 0.05) were identified with PeakView 1.2 Software. Results: Ten differential components, including 6-gingerol, 8-gingerol, and 10-gingerol, were identified between the ginger group and dried ginger group; 13 differential components, including 6-shogaol, 10-gingerol, and zingiberone, were identified between the dried ginger group and ginger charcoal group. Conclusions: The main differential components between the ginger and dried ginger groups and the dried ginger and ginger charcoal groups were gingerols and diphenylheptanes. Based on metabolomics analysis of the chemical composition of ginger's medicinal materials, effects, and other related factors, it is recommended that 6-gingerol, 6-shogaol, and zingiberone should be used as indicative components for the respective quality evaluation of ginger, dried ginger and ginger charcoal. The results of this study may provide a basis for the reasonable quality evaluation of ginger medicinal materials.